(untitled) (Muitas Vozes, 2024)
In this essay, we analyse the work “As mães da Síria” (2017) by the poet Isabel Aguiar. This work was inspired by the paintings in the exhibition “O Tempo dos Sonhos”, by Mario Rita (2005). His poetic style addresses various relationships with the outside and rethinks the inbetween places and the ruins of a patriarchal world that reproduces the outcasts. His poetry thematizes and reverberates the traces of the outside in its most radical and political sense. With the help of Isabel Aguiar, we note that ruin is a paradoxical concept, like the presence of the outside. This brings us to Blanchot. According to Blanchot, the poet is always outside himself because “the poem is exile”.